Opera, Audio Technologies, and Audience Practices in the Late Nineteenth Century: The Case of Jules Verne (Sound Stage Screen, 2023)
This article analyzes several novels and short stories by Jules Verne devoted to opera, audio technologies, and audience practices. This portion of Verne’s output is particularly thought-provoking for the cultural history of recording technologies, technologically-influenced listening practices, audience behavior, and music fandom. As often in Verne, the exploration of art worlds is connected with the exploration of technological inventions, such as recording and broadcast technologies. This article focuses in particular on L’Île à hélice (1895) and Le Château des Carpathes (1892). These novels are linked to their wider cultural, social, and technological contexts as well as to recent theoretical frameworks developed in the field of opera studies, sound studies, media studies, fan studies, the cultural history of technology, and Verne studies. The aim of the article is to shed light on the genesis of the relation between operatic audiences and audio technologies through a survey of Jules Verne’s visionary and imaginative narratives.
Keywords: Jules Verne; opera; audio technologies; audience practices; theatre